Factors That Cause Work Engagement in the Millennial Performance in BUMN - Akhmad Fani Rakhim (Proceedings of The ICECRS, 2020)
Various research results reinforce the importance of having human resources engaged in their work. Employees who are engaged in their work will benefit both in terms of individuals, groups and organizations. In fact, the level of employee engagement in Indonesia is relatively low. Even the level of work engagement in the millennial workforce is at the lowest level. This study aims to determine the factors that influence the work engagement of millennial employees in BUMN. Participants consist of 3 BUMN's employees, male and have a working period of between 5 and 15 years. Data obtained through semi-structured interviews and analyzed qualitatively. The results of this study indicate that work engagement in the millennial workforce is sourced from job resources and personal resources. Job resources include work environment, family atmosphere, career opportunities, rewards, valuable experiences and challenges; while personal resources include self efficacy. The millennial workforce also does job crafting by integrating their lives with their work.